FSKKP organised third ICSECS Conference 2013 - Noraniza, Samat
Faculty of Computer Systems & Software Engineering (FSKKP), Universiti Malaysia Pahang (UMP) organised the 3rd International Conference on Software Engineering and Computer Systems (ICSECS - 2013) at Astaka Hall, UMP Gambang campus on August 22, 2013.